2019
DOI: 10.29271/jcpsp.2019.09.823
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Postmenopausal Vitamin D Level, Menopausal Symptoms and Sexual Functions

Abstract: Objective: To determine whether vitamin D levels correlate with menopausal symptoms and female sexual functions. Study Design: A cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…This was rendered to their recruitment of breast cancer survivors on aromatase inhibitors. Another contradictory finding was reported [10]. This contradiction would be explained by their inclusion of women with vitamin D deficiency while the current study did not.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This was rendered to their recruitment of breast cancer survivors on aromatase inhibitors. Another contradictory finding was reported [10]. This contradiction would be explained by their inclusion of women with vitamin D deficiency while the current study did not.…”
Section: Discussioncontrasting
confidence: 71%
“…Thus, neurological and psychological actions of vitamin D have been claimed [29]. Additionally, another study reported that chronic diseases were related to the increased severity of menopausal symptoms [10,30]. This would be rendered to the addition of symptoms related to these illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, high levels of vitamin D might protect against somatic symptoms, especially hot flashes, during menopause. In addition, in a recent study, it was mentioned that menopausal symptoms are less common in women with normal vitamin D levels than in women with vitamin D deficiency (23).…”
Section: Discussionmentioning
confidence: 99%
“…Each 10 ng/mL (25 nmol/L) increase in 25(OH)D was associated with a 4% (OR 0.96, 95% CI 0.94-0.99) and 8% (OR 0.92, 95% CI 0.87-0.98) decrease in depression risk (data from cross-sectional and cohort studies, respectively) [24]. Sexual function was inversely associated with 25(OH)D concentrations in a cross-sectional study of 303 postmenopausal women (mean age 53.8 ± 6.2 years) [25].…”
Section: Menopausal Symptomatologymentioning
confidence: 99%